1993
DOI: 10.1002/j.2050-0416.1993.tb01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fatty Acid Hydroperoxides Produced During the Production of Wort

Abstract: Linoleic and linolenic acid hydroperoxides in malt, mash, or wort were determined with high sensitivity and high selectivity by the chemiluminescence-high performance liquid chromatography (CL-HPLC) method using isoluminol-microperoxidase solution as a luminescing reagent. The determination limit of this method for both hydroperoxides was 0.1 iM in mash or wort. During the mashing in a laboratory mash bath, the hydroperoxides started to increase just after mashing-in, reached a maximum at 65°C, and then decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…Most residual activity was represented by the LOX 1 isoenzyme which mainly produced the 9-hydroperoxide, precursor of trans 2 nonenal in beer. This supported the hypothesis of Kobayashi et al (1993a) who presented LOX as the main factor involved in off flavor production.…”
Section: Some Kinetic Properties Of Lox 1 and Loxsupporting
confidence: 89%
“…Most residual activity was represented by the LOX 1 isoenzyme which mainly produced the 9-hydroperoxide, precursor of trans 2 nonenal in beer. This supported the hypothesis of Kobayashi et al (1993a) who presented LOX as the main factor involved in off flavor production.…”
Section: Some Kinetic Properties Of Lox 1 and Loxsupporting
confidence: 89%
“…13), nonetheless we were confident in our ability to measure 10-20 nmol of hydroperoxide. This compares favourably with chromatographic methods described by others 24 . In control mashes to which cumene hydroperoxide was added, we were unable to recover the addition in the wort.…”
Section: ]Hvstivs\mhiwsupporting
confidence: 78%
“…Because we were unable to recover added hydroperoxide we are not in a position to say whether hydroperoxides are, or are not, produced during mashing of these malts under the conditions studied. However Kobayashi et al 24 found that hydroperoxides did decrease in level during mashing and wort separation.…”
Section: ]Hvstivs\mhiwmentioning
confidence: 97%
“…At the time of sampling, the entire mash was poured into a beaker with addition of ice-cold distilled water (200 ml) and solid CO, (5 g). The mixture was extracted with diethyl ether/light petroleum (bp 40-60°C) 1 : 1, v/v; 500 ml: Kobayashi et al 1993a). Solvent was removed under reduced pressure from a portion (200 ml) of the extract which was then dissolved in methanol/chloroform (8 : 2, v/v; 10 ml) before analysis by CL-HPLC.…”
Section: Extraction Of Fatty Acid Hydroperoxides From Laboratory-scalmentioning
confidence: 99%